1995
DOI: 10.1086/133634
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Long-Term Optical Base-Level Fluctuations in Three Classes of AGN

Abstract: The long-term optical light curves of many active galactic nuclei (AGN) display smooth, cyclic changes in level on time scales of years. Earlier work by Smith et al. (AJ, 105, 437, 1993) estimated the time scales of this previously undiscussed phenomenon for a sample of 60 classical radio-loud quasars. The present study extends the analysis to three additional groups of AGN: the BL Lacertids, the compact galaxies, and the radio-quiet quasars. The average time scale of the BL Lacertids is approximately equal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 16 publications
3
31
1
Order By: Relevance
“…Marchenko et al (1996) found a statistically significant long term component with P = 7.8 ± 0.2 yr in the 20 year duration light curve using the whitening of the time series method. Smith & Nair (1995) found a period of 7.7 yr using a 20 yr duration light curve using Fourier analysis thus, consistent with Marchenko et al (1996). Later, Fan et al (1998) obtained a long term period of 14 yr using the Jurkevich method on the optical light curve.…”
Section: Bl Lacertaesupporting
confidence: 88%
“…Marchenko et al (1996) found a statistically significant long term component with P = 7.8 ± 0.2 yr in the 20 year duration light curve using the whitening of the time series method. Smith & Nair (1995) found a period of 7.7 yr using a 20 yr duration light curve using Fourier analysis thus, consistent with Marchenko et al (1996). Later, Fan et al (1998) obtained a long term period of 14 yr using the Jurkevich method on the optical light curve.…”
Section: Bl Lacertaesupporting
confidence: 88%
“…After the deep minimum observed in 1972-74, the brightness of ON 231 began to increase following a slow, quasi linear trend, with a small outburst visible in the period 1979-1981. Superimposed on this trend there are complex variations characterized by a total amplitude of about one magnitude and a time scale of about 4 years (Smith & Nair 1995). From a visual inspection of the historic light curve, Pollock (1974) suggested a possible quasi-periodicity of about 14 years for the outbursts, a value which agrees with the period of 13.6 ± 1.3 years recently proposed by Liu et al (1995).…”
Section: The Historical Light Curve Of On 231supporting
confidence: 61%
“…It is known that the source shows variability on time scales from hours to years (see, e.g., Smith & Nair 1995;Xie et al 1992). But previously published light curves are not so densely sampled to allow a sufficiently detailed study of structure and occurrence of the short term variations.…”
Section: Introductionmentioning
confidence: 99%
“…Note that some other BL Lac objects (e.g. 0215 + 015), for which detections of broad emission lines have been reported, are similarly characterized by long term decreasing luminosity trends (Smith & Nair 1995). A spectroscopic monitoring of this object, as well as of other blazars in a low state, would be highly useful to clarify the relation of the line emission with the variations of the ionizing continuum.…”
Section: Discussionmentioning
confidence: 77%